Regenerative and reparative effects of human chorion-derived stem cell conditioned medium on photo-aged epidermal cells. Issue 8 (17th April 2016) - Li, Qiankun; Chen, Yan; Ma, Kui; Zhao, Along; Zhang, Cuiping; Fu, Xiaobing
ABSTRACT: Epidermal cells are an important regenerative source for skin wound healing. Aged epidermal cells have a low ability to renew themselves and repair skin injury. Ultraviolet (UV) radiation, particularly UVB, can cause photo-aging of the skin by suppressing the viability of human epidermal cells. A chorion-derived stem cell conditioned medium (CDSC-CNM) is thought to have regenerative properties. This study aimed to determine the regenerative effects of CDSC-CNM on UVB-induced photo-aged epidermal cells. Epidermal cells were passaged four times and irradiated with quantitative UVB, and non-irradiated cells served as a control group. Cells were then treated with different concentrations of CDSC-CNM. Compared to the non-irradiated group, the proliferation rates and migration rates of UVB-induced photo-aged epidermal cells significantly decreased (p < 0.05) with increasing intracellular radical oxygen species (ROS) generation and DNA damage. After treatment with CDSC-CNM, photo-aged epidermal cells significantly improved their viability, and their ROS generation and DNA damage decreased. The secretory factors in CDSC-CNM, including epidermal growth factor (EGF), transforming growth factor-β (TGF-β), interleukin (IL)-6, and IL-8 and the related signaling pathway protein levels, increased compared to the control medium (CM). The potential regenerative and reparative effects of CDSC-CNM indicate that it may be a candidate material for the treatment of prematurely aged skin. The functions of the secretory factors and the mechanisms of CDSC-CNM therapy deserve further attention.